2023
DOI: 10.13057/biodiv/d231220
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Leopard cat (Prionailurus bengalensis) distribution in the Cisokan Hydropower Plant, West Java, Indonesia

Abstract: Abstract. Husodo T, Megantara EN, Mutaqin AZ, Kendarto DR, Wulandari I, Shanida SS. 2022. Short Communication: Leopard cat (Prionailurus bengalensis) distribution in the Cisokan Hydropower Plant, West Java, Indonesia. Biodiversitas 23: 6247-6253. Globally, leopard cats (Prionailurus bengalensis) can be found in various land cover types. Information about leopard cats is still low in Indonesia, especially in Java. Java Island has high human activities that impact leopard cats, such as the UCPS hydropower develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 20 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…The literature review was conducted through Researchgate with the keywords Cisokan, UCPS, leopard cats, Prionailurus bengalensis, the biodiversity management plan, and the forest partnership framework. We reviewed several research papers and technical reports, including Shanida et al (2018b), Husodo et al (2019b); CESS (2020) unpublished; CESS (2021); Husodo et al (2022), andShanida et al (2023).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature review was conducted through Researchgate with the keywords Cisokan, UCPS, leopard cats, Prionailurus bengalensis, the biodiversity management plan, and the forest partnership framework. We reviewed several research papers and technical reports, including Shanida et al (2018b), Husodo et al (2019b); CESS (2020) unpublished; CESS (2021); Husodo et al (2022), andShanida et al (2023).…”
Section: Methodsmentioning
confidence: 99%
“…Based on leopard cats' distribution from 2017 to 2022 (Figure 2), leopard cats' habitats overlap in the UCPS area. Of the 56 findings, 35 (63%) were found within the UCPS area, such as in the lower dam, upper dam, permanent access road, temporary access road, and sliding gate (Shanida et al 2018b;Husodo et al 2022). Husodo et al (2022) revealed that leopard cats still use the same areas as their habitat after 5-10 years, covering an area of 10 km 2 in the UCPS area.…”
Section: Overlapping Leopard Cats' Habitat and Ucps Areamentioning
confidence: 99%
See 3 more Smart Citations